A Perception Study of Taxable Persons on Goods and Services Tax in the Guwahati City of Assam - Mour, Dinesh Kumar; Paul, Tarak (Arthshastra Indian Journal of Economics & Research, 2021)
Goods and Services Tax (GST) implemented in India sought to formalize the Indian economy by making the market more competitive and thereby auguring economic growth. However, compliance function with regard to any system of taxation can be executed only by first properly understanding the system. A study of businessmen’s perception, across their occupation types, be it the manufacturers, traders, and service providers towards the implementation of Goods and Services Tax can assist the government both in better policy making as well as enhancing society’s confidence towards the government in implementing the system. The present study was conducted with a sample of 104 taxable persons in Guwahati, Assam identified by snowball sampling, and an attempt was made to understand the differences in the perception of taxable persons on Goods and Services Tax attributes across their occupation types. Six attributes of Goods and Services Tax : Concept, Structure, Procedure, Administration, Compliance, and Ease of Doing Business were the subject matter of the study. The findings of the study revealed that there did not exist significant differences in terms of Goods and Services Tax attributes as perceived by the taxable persons across their occupation types. With some simplification in the structural and procedural aspects and improvement in administration, better compliance can be ensured. The findings revealed that there is reasonable clarity amongst the taxable persons as regard the provisions of the Goods and Services Tax. Further improvements in the legislation through proper policy framing and better implementation will result in improved compliance.